2010
DOI: 10.1177/0748233710383743
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effect of occupational exposure to cadmium

Abstract: Many studies proved the genotoxic effect of cadmium (Cd) exposure and highlighted the importance of the cytogenetic studies as a sensitive and effective means for early detection of Cd-induced mutagenicity. The relationship between occupational exposure to Cd and increased risk of cancer, particularly lung cancer, has been explored in number of epidemiological studies. The aim of this study is to assess the role of chromosomal abnormalities and sister chromatid exchange as sensitive indicators for the genotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…This result suggests that Cd might have the potential to induce AID in somatic cells via the activation of NF-jB. AID expression in somatic cells has been shown to lead to cytogenetic alteration, which is consistent with the results of cytogenetic studies among subjects with occupational exposure to Cd [21,22].…”
Section: Discussionsupporting
confidence: 86%
“…This result suggests that Cd might have the potential to induce AID in somatic cells via the activation of NF-jB. AID expression in somatic cells has been shown to lead to cytogenetic alteration, which is consistent with the results of cytogenetic studies among subjects with occupational exposure to Cd [21,22].…”
Section: Discussionsupporting
confidence: 86%
“…Genotoxicity was also induced by the exposure of zebra fish to Cd at environmentally relevant doses [4]. Regardless of the time of exposure, human contact with Cd significantly increased chromosomal aberrations and exchange of sister chromatids in all age groups [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Micronuclei formation in humans is associated with various medical conditions (LUZHNA et al, 2013). Human contact significantly increased chromosomal aberrations and sister chromatid exchange in all age groups (ABRAHIM et al, 2011). CONCLUSIONS In these experiments, we showed that CdCl2 treatment significantly increased the frequency of micronuclei in polychromatic erythrocytes (PCE) of bone marrow of DA and AO rats depending on concentration, gender, age and strain.…”
Section: Discussionmentioning
confidence: 66%